1997
DOI: 10.1007/s004660050207
|View full text |Cite
|
Sign up to set email alerts
|

On crack path stability in a layered material

Abstract: Crack paths in an elastic layer on top of a substrate are considered. Crack growth is initiated from an edge crack in the layer. The plane of the initially straight crack forms an angle to the free surface. The load consists of a pair of forces applied at the crack mouth and parallel to the interface. Crack paths are calculated using a boundary element method. Crack growth is assumed to proceed along a path for which the mode II stress intensity factor vanishes. The inclination and the length of the initial cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Gunnars et al 12 performed the same type of experiments to study the path of non‐branching cracks growing towards an interface between the PC and a stiffer substrate. (Results from the study are also presented in Gunnars et al 13 ) They found that cracks did not follow straight paths, but deflected gradually avoiding the interface. Several of the tests in their study gave branched cracks, but these were disregarded.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Gunnars et al 12 performed the same type of experiments to study the path of non‐branching cracks growing towards an interface between the PC and a stiffer substrate. (Results from the study are also presented in Gunnars et al 13 ) They found that cracks did not follow straight paths, but deflected gradually avoiding the interface. Several of the tests in their study gave branched cracks, but these were disregarded.…”
Section: Introductionmentioning
confidence: 52%
“…Broberg, 23 meaning that a crack will follow a path where K II = 0. In numerical analysis of the experimental results, Gunnars et al , 12,13 also found that dissolution driven SC cracks grow predominantly along a mode I path. In this study, it is observed that the cracks always divide into two branches.…”
Section: Theoretical Considerationsmentioning
confidence: 91%
“…8. Gunnars et al (1997) presented another definition of directional instability by divergence of the initially adjacent crack trajectories as common in nonlinear dynamics. A crack path is directionally unstable, if a small path deviation d 0 at the arc length s 0 leads to greater path deviation d at a sufficiently large arc length s, such that…”
Section: Definition Of Global Directional Stabilitymentioning
confidence: 98%
“…Polycarbonate is also chosen because it has proven usable in similar studies. Gunnars et al (1994Gunnars et al ( , 1997 used this material combination to study non-branching crack propagation directions.…”
Section: Materials and Preparationmentioning
confidence: 99%